Germline PALB2 mutation analysis in breast–pancreas cancer families. Issue 8 (17th March 2011) - Stadler, Zsofia K; Salo-Mullen, Erin; Sabbaghian, Nelly; Simon, Jennifer A; Zhang, Liying; Olson, Sara H; Kurtz, Robert; Offit, Kenneth; Foulkes, William D; Robson, Mark E; Tischkowitz, Marc
Abstract : Background: Germline mutations in the PALB2 gene have been implicated in both breast cancer and pancreatic cancer susceptibility. The extent to which PALB2 mutations account for cancer susceptibility in breast–pancreas cancer families is unknown. Methods: High Resolution Melting analysis and Multiplex Ligation-dependent Probe Amplification were performed to investigate the prevalence of PALB2 mutations in patients with either a personal history of both breast and pancreatic cancer or a personal history of breast cancer and a family history of a first degree relative with pancreatic cancer. Results: No PALB2 mutations were identified in 77 breast–pancreas cancer families, which included 22 probands with a personal history of both breast and pancreatic cancer. Conclusion: Mutations within the PALB2 gene are rare events that do not account for a substantial proportion of cancer susceptibility in breast–pancreas cancer families. Routine screening of breast–pancreas cancer families for the presence of PALB2 mutations appears to be low yield.